Application of Propofol in Oral and Maxillofacial Surgery Anesthesia Based on Smart Medical Blockchain Technology - Yu, Zhaoxiang (J Healthc Eng, 2021)
The rapid development of intelligent computer technology has promoted the improvement of people's living standards and the application of the entire intelligent system. In modern medicine, doctors use their accumulated experience and medical knowledge to diagnose diseases and draw conclusions. In order to effectively inherit the diagnosis experience accumulated by doctors, R&D personnel put forward the idea of using artificial intelligence technology to develop an intelligent auxiliary medical diagnosis system. Aiming at the abovementioned machine-learning problems in the medical field, this article mainly introduces the application research of propofol in oral and maxillofacial surgery anesthesia based on smart medical blockchain technology. This paper proposes a research method based on smart medical blockchain technology to assist propofol in oral and maxillofacial surgery anesthesia, including support vector machine data classification algorithm, decision tree data classification algorithm, and machine-learning-based LSTM neural network. Research experiments on the application of intelligent medical aid propofol in oral and maxillofacial surgery anesthesia are conducted. The experimental results in this paper show that the response time of the general business logic interface of the application system of propofol in oral and maxillofacial surgery anesthesia based on smart medical blockchain technology is about 41 milliseconds, which can better help doctors in anesthesia and related treatments.